A SEMIOTIC ANALYSIS OF FEMINISM THEORIES IN THE MOVIE OF 7 HATI 7 CINTA 7 WANITA DIRECTED BY ROBBY ERTANTO - Linta Wafdan Hidayah; Alisa Qotrunada (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2021)
The movie 7 Hati 7 Cinta 7 Wanita directed by Robby Ertanto that presents a representation of seven women in the Indonesian context through certain signs, concepts, thoughts, and language. This representation can be in the form of a depiction of physical or psychological violence, subordination, workload, power, or women's reproductive rights. The research method used Roland Barthes' semiotic analysis model and constructivist paradigm approach. Barthes' theory represents two ideological signs that he put forward, namely the denotative sign system or the connotative sign system: A denotative sign, which is a more rigorous descriptive system than the connotative sign it has described, is the result of the existing signifier image and the signified concept. for example vegetables and milk are markers and healthy and strong are markers. Whereas A connotative sign is a sign that experiences a shift in its historical meaning due to a change in meaning. It can be influenced by a change in culture or terminology, an event that occurs in a situation, or even just an evolution.The results of this study indicate that in the movie7 Hati 7 Cinta 7 Wanita contains at least three points of findings: (1) aspects of female domestication and gender politics, which encourage women to be placed in traditional positions as housewives, (2) aspects of segregation, namely placing women in a weak position in relation to men, (3) many women experience the reality that places them in subordinate positions.